Does Diplomatic Influence Pay? A Gravity Model Estimation of the Effect of Morocco’s Soft Power Assets on its Bilateral Trade Volumes in Africa - Hamid Fayou; Nabil Boubrahimi (Daengku: Journal of Humanities and Social Sciences Innovation, 2026)
This study investigates whether Morocco’s soft power assets its (cultural religious, economic, and diplomatic influence) translate into tangible economic benefits in the form of increased bilateral trade with African partners. Using an augmented gravity model of trade estimated with Poisson Pseudo-Maximum Likelihood (PPML) for a panel of 45 African countries over the period 2010–2024, we quantify the impact of various soft power proxies on Morocco’s trade flows. The results indicate that soft-power instruments, particularly cultural diplomacy, religious ties, and active peacekeeping contributions, exert a statistically significant and economically meaningful positive effect on trade volumes, even after controlling for traditional gravity determinants such as GDP, distance, and colonial links. The findings suggest that Morocco’s deliberate soft-power strategy in Africa is not merely a political tool but also a viable economic diplomacy that can enhance regional trade integration. Policy implications include the continued investment in soft-power channels as a complement to traditional trade liberalization measures.